Biodegradation and detoxification of reactive orange 16 by Candida sake 41E - Ruscasso, Maria Florencia; Cavello, Ivana Alejandra; Butler, Matias; Lopez Loveira, Elsa Gabriela; Curutchet, Gustavo Andres; Cavalitto, Sebastian Fernando (Bioresource Technology Reports)
This investigation was aimed at studying reactive orange 16- (RO-16) dye biodegradation by the Antarctic yeast Candida sake 41E. Dye decolorization reached 94.3% (an initial 100 mg.l−1) within 48 h in a stirred-tank bioreactor at a specific decolorization rate of 0.09 mg.RO-16.g−1.h−1. The presence of reactive dye in the medium did not affect yeast growth. A specific growth rate (μ) of 0.09 h−1 and biomass yield (Yx/s) of 0.23 CmolX.CmolS−1 were obtained. Reversed-phase ultrahigh-performance-liquid-chromatography–mass-spectrometry analysis was performed to investigate the by-products generated during the biodegradation. Five yeast-catalyzed reaction products of RO-16 were identified and a biodegradation pathway for this azo dye thus proposed. In addition, the toxicity of the dye and by-products generated was assessed with Lactuca sativa L. seeds, confirming the phytotoxicity of RO-16 and its decrease after 48 h of treatment with C. sake 41E. Fil: Ruscasso, Maria Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Butler, Matias. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental. - Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigación e Ingeniería Ambiental; Argentina Fil: Lopez Loveira, Elsa Gabriela. Universidad Nacional de San Martín. Instituto de ...